PENGARUH MODEL PEMBELAJARAN MAKE A MATCH BERBANTUAN MEDIA PUZZLE TERHADAP KEMAMPUAN NUMERASI MATERI PECAHAN PADA SISWA KELAS III SDN PLAMONGANSARI 02 - Pujiati, Shela Sri; Nuvitalia, Duwi; Nugraha, Yusuf Fuad (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to determine the effect of implementing the Make A Match Learning Model assisted by Puzzle media on the numeracy abilities of class III students at SDN Plamongansari 02 Semarang. The method used in this research is quantitative with a one-group pretest-posttest design. The research sample consisted of class III students at SDN Plamongansari 02 who underwent a pretest before implementing the learning model and a posttest afterwards. The data obtained were analyzed using descriptive statistical techniques and paired samples t-test. The research results showed that there was a significant increase in students' numeracy abilities after implementing the Make A Match Learning Model with the help of Puzzle Media. The average student score increased significantly from 49.4118 on the pretest to 81.7647 on the posttest. The statistical test shows the Sig value. (2-tailed) is 0.000, which is smaller than the significance level α = 0.05, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This shows that the learning model applied has a significant influence on students' numeracy abilities